PENANAMAN NILAI KARAKTER TANGGUNG JAWAB PADA SISWA KELAS IIIC DI SDN 003 LOA JANAN ILIR - Fitrianingsih; Nurul Hikmah; Nurdin Arifin (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2026)
A b s t r a c t This study aims to determine the instilling of the responsibility character value in class III C students at SDN 003 Loa Janan Ilir. The research method used is qualitative, with data collection techniques involving observation, interviews, and documentation. The subjects in this study are the principal, the grade IIIC teacher, and four grade IIIC students. The data validity test in this study uses source triangulation. The research results show that; (1) the instilling of the responsibility character value has been implemented gradually and consistently through various strategies. (2) The principal supports with evaluation programs, awards, and class visits. (3) Teachers play an active role through routine activities such as cleanliness duties, individual assignments, motivation reinforcement, and exemplification. (4) Students show a good understanding of responsibility, but its implementation still faces obstacles such as lack of discipline and bad habits from the home environment. Nevertheless, the school applies educational sanctions and positive appreciation. The lack of parental involvement becomes a significant barrier. This value instilling has a positive impact on students' academic achievement. Overall, the efforts to instill responsibility values at SDN 003 Loa Janan Ilir are going well, but need to be improved through close cooperation between schools, teachers, parents, and the surrounding environment for sustainable character formation. Keywords: Instilling Character Values; Responsibility; Elementary School Students